2023
DOI: 10.1002/adfm.202212452
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Micro‐/Nanomotors: Design, Imaging, and Disease Treatment

Abstract: Untethered mobile micro-/nanomotors (MNMs), as newly-emerging attractive and versatile nanotechnologies, are expected to be the next-generation disease treatment tools, for breaking through the limitations of conventional passive drug delivery manner. However, the advances in these fascinating platforms have been hampered by the complexity of the biological environment and the particularity of disease microenvironment. Consequently, specific design strategies and clinical imaging techniques are essential to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 239 publications
(340 reference statements)
0
14
0
Order By: Relevance
“…The results depicted in Figure 4B,C demonstrate that the tumor volume was partially suppressed in the PDT ( 5) and PTT (6) treated groups compared to those of control groups (1)(2)(3)(4). This suggested that mPPy@COF-Por could partially eradicate tumor cells under single light irradiation.…”
Section: Anticancer Performance Of Mppy@cof-por Nanomotormentioning
confidence: 87%
See 1 more Smart Citation
“…The results depicted in Figure 4B,C demonstrate that the tumor volume was partially suppressed in the PDT ( 5) and PTT (6) treated groups compared to those of control groups (1)(2)(3)(4). This suggested that mPPy@COF-Por could partially eradicate tumor cells under single light irradiation.…”
Section: Anticancer Performance Of Mppy@cof-por Nanomotormentioning
confidence: 87%
“…Synthetic nanomotors, which can convert various energy sources into mechanical motion to achieve complex tasks in solution, have gained more and more attention [1,2] Compared with chemical and enzyme-powered nanomotors, [3,4] physical nanomotors driven by external fields, such as magnetic, ultrasound, light, and electric fields, offer more advantages for biomedical applications. For example, they are not limited by the availability of DOI: 10.1002/adhm.202301645 external chemical fuels (e.g., hydrogen peroxide (H 2 O 2 ), urea, or glucose).…”
Section: Introductionmentioning
confidence: 99%
“…Motile micro-/nanorobots (MNRs) are micro-/nanodevices capable of autonomously propelling and navigating in various liquid media by harvesting energy from surrounding chemicals or external fields. Purely through local communications, MNRs can further self-organize into cohesive groups with emerging collective behaviors that individual robots lack, such as cooperative propulsion, high robustness, dynamic reconfigurations, and high imaging contrast. With mobilities and collective behaviors, MNRs are envisioned to perform biomedical tasks in a “motile-targeting” manner, revolutionizing modern biomedicine in contrast to traditional passive and active targeting strategies. Particularly, when equipped with a photothermal engine or incorporated with additional photothermal nanoagents, MNRs have demonstrated the ability to perform efficient targeted PTT. For instance, self-thermophoretic Janus micromotors with a gold cap have been demonstrated to weld superficial wounds in bleeding animals . Moreover, near-infrared (NIR) laser-propelled parachute-like poly­(divinylbenzene)/Pt nanomotors can deliver antifungal drugs to deep skin tissues and obliterate plankton Candida albicans and mature biofilms by combining pharmacological therapy and photothermal therapy .…”
Section: Introductionmentioning
confidence: 99%
“…into autonomous motions and forces. [10][11][12][13][14] Over the past twenty years, artificial micro/nanomotors have evolved into a cross-cutting frontier of materials, nano and biomedical sciences. Micro/ nano dimensions, ease of modification and active movement ability enable the artificial micro/nanomotors to perform certain complex tasks including cargo delivery, [15][16][17][18][19] noninvasive surgery, [20][21][22][23][24][25][26][27][28][29] cell manipulation, [30][31][32] bioimaging, 18,33 and biosensing [34][35][36][37][38][39] at the microscopic scale.…”
Section: Introductionmentioning
confidence: 99%
“…40 In the past decade, remarkable advancements have been made in the burgeoning field of artificial micro/nanomotors for biosensing, signifying its rapid growth and notable accomplishments. 14,[40][41][42] The objective of this review is to shed light on the progression of nucleic acid biosensing through the utilization of micro/nanomotors. Initially, we provide a concise overview of the prevailing techniques employed to propel micro/nanomotors for nucleic acid biosensing.…”
Section: Introductionmentioning
confidence: 99%